EFEKTIVITAS PROGRAM POSYANDU SRI REJEKI DALAM PENURUNAN STUNTING DI DESA KENDALPECABEAN KECAMATAN CANDI KABUPATEN SIDOARJO - Christanty Dwi Kurniawati; Hendra Sukmana (Halu Oleo University, 2025)
This study aims to analyse the effectiveness of the Sri Rejeki Integrated Health Post (Posyandu) Program in reducing stunting in Kendalpecabean Village, Candi District, Sidoarjo Regency, using descriptive qualitative methods. Data collection techniques were conducted through observation, interviews, and documentation with purposive sampling, while analysis used the Miles and Huberman model, which includes data reduction, presentation, and conclusion drawing. The results showed that in terms of targeting accuracy, toddler participation was still low because not all attended the Posyandu. In terms of socialisation, the program has been implemented quite well, although community understanding of the information is still limited. In terms of objectives, program implementation has not been fully achieved due to the lack of competence of cadres. Meanwhile, the monitoring aspect is considered quite effective thanks to the assistance and supervision of village midwives in each activity. Overall, the Sri Rejeki Integrated Health Post (Posyandu) program plays a role in efforts to reduce stunting, but still requires increased community participation, increased cadre capacity, and a more optimal communication strategy to achieve the program's objectives.